Influence of Residential Combustion on Total Gaseous Mercury (TGM) Levels: a Preliminary Study at an Urban Megacity in Vietnam - Nguyen, Ly Sy Phu; Pham, Thi Dieu Huong; To, Thi Hien; Tran, Anh Ngan; Tran, Vu Kiet; Nguyen, Thao Nguyen (Journal of Technical Education Science, 2023)
Mercury (Hg) is a global pollutant that has gained monumental attention in recent decades due to its neurotoxicity and great bioaccumulation features. The atmosphere plays a key role in the movement of Hg in the environment, and residential combustion is a significant contributor to atmospheric Hg. However, there is a severe lack of research on the impact of Hg emissions from residential combustion in Southeast Asia (SEA). This study focused to illustrate the contribution of residential combustion on the level of total gaseous mercury (TGM) in a tropical megacity in southern Vietnam by conducting a short field campaign in February 2023. The mean TGM concentration during the study period was 2.27 ± 0.81 ng m-3, in which daytime TGM level (7 am – 7 pm, 2.56 ± 0.80 ng m-3) was significantly higher than at night (7 pm – 7 am, 1.58 ± 0.28 ng m-3), which could be attributed to local burning activities. The TGM concentration was also increased because of the increase in burning activities (i.e. burning joss paper and incense) during the Lantern Festival. Backward trajectory analysis suggested the domination of regional background air mass in the study area, implying that TGM concentration variation is mostly associated with local influences. We estimated that residential combustion caused a rise of around 70% in TGM concentration at the sampling site. Overall, this is the first study to illustrate the importance of Hg emissions from residential combustion in urban SEA region, laying a background for upcoming studies in atmospheric Hg in this region.